A comparative study of efficacy and safety of intramuscular carboprost and intravaginal misoprostol for cervical priming prior to first trimester surgical abortion - Mathuriya, Gayatri; Verma, Neha; Pandey, Shivangi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: MTP Act no 34 of 1971 has been defined as Legal termination of pregnancy before the age of viability of fetus that is 20 weeks of gestation. There is a need to find a medical agent which can help in the process of abortion by speeding it up, with minimal side effects. The objective of this study was to compare the efficacy of I.M carboprost and intravaginal Misoprostol and to evaluate the safety profile of I.M carboprost and Intravaginal Misoprostol. To compare the cervical dilatation caused by I.M carboprost and intravaginal Misoprostol and to compare the blood loss and adverse effects of I.M carboprost and Intravaginal Misoprostol. Methods: Prospective randomized experimental study including pregnant women up to 12 weeks of gestation opting for M.T.P. Study conducted on 200 patients selected from patients admitted in MGM Medical College and M.Y. Hospital, Indore and Kalyanmal Hospital, Indore during the period July 2014 to March 2015. They were randomly divided into 2 groups. Group A who received intramuscular injection of 250 mcg of caboprost or Group B,which received 400 mcg of vaginal Misoprostol 4 hours prior to suction evacuation. Results: Intravaginal misoprostol achieves better cervical dilatation compared I.M carboprost which is statistically significant. Misoprostol is associated with higher blood loss as compared to I.M carboprost which is associated with nausea/vomiting & more likelihood of loose stools and abdominal cramps which is proved statistically. Conclusions: Intravaginal misoprostol is associated with higher blood loss as compared to I.M carboprost which is significant but intravaginal misoprostol achieves more cervical dilatation and causes less adverse events than I.M carboprost which is statistically more significant and therefore intravaginal misoprostol is the drug of choice for cervical priming prior to surgical abortion in terms of both efficacy and safety.